CHARITY BEGINS – BUT DOES NOT END – AT HOME Khosa v Minister of Social Development; Mahlaule v Minister of Social Development 2004 6 BCLR 569 (CC) - Letlhokwa George Mpedi (Obiter, 2022)
Social assistance has emerged, within a broader social security system, as an important part of those measures that prevent and/or alleviate destitution in South Africa. Social assistance, as defined by the Committee of Inquiry into a Comprehensive System of Social Security for South Africa (Committee of Inquiry into a Comprehensive System of Social Security for South Africa Transforming the Present – Protecting the Future: Consolidated Report (2002) 36), means “state-provided basic minimum protection to relieve poverty, essentially subject to qualifying criteria on a non-contributory basis”. In April 2004, more than 7.9 million people were reported to benefit from the social grants (National Treasury (Republic of South Africa) Trends in Intergovernmental Finances: 2000/01-2006/07 (2004) 74). In most instances, predominantly in black households, grants (especially old-age grants) are the only family income. Old-age grants in particular are used not only to see the elderly through their old-age, but they also stretch far beyond that to cater for the needs of the family. This important scheme, particularly its scope of coverage, has been a source of recent social security law debates. Central to these debates was the issue of non-citizens’ (non-)entitlement to the same social assistance benefits as citizens. This subject has no clear-cut answer(s).